2006
DOI: 10.1007/s10719-006-5439-7
|View full text |Cite
|
Sign up to set email alerts
|

Localisation and distribution of O-acetylated N-acetylneuraminic acids, the endogenous substrates of the hemagglutinin-esterases of murine coronaviruses, in mouse tissue

Abstract: Infections by mouse hepatitis viruses result in disease of the liver, the gastrointestinal tract, respiratory tract, and the central nervous system. Coronaviruses related to mouse hepatitis virus express a hemagglutinin-esterase surface glycoprotein, which specifically hydrolyses either 5-N-acetyl-4-O-acetyl neuraminic acid (Neu4,5Ac(2)) or 5-N-acetyl-9-O-acetyl neuraminic acid (Neu5,9Ac(2)). Moreover, these sialic acids represent potential cellular receptor determinants for murine coronaviruses. Until now, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 55 publications
4
26
2
Order By: Relevance
“…Similar region specificity was observed in the mouse intestine, along with wide variations in sialic acid amounts and their various alternate chemical forms in the liver and central nervous system compared to the intestinal tract (18). Those authors also found substantial amounts of intestinal Neu4,5Ac 2 , which might not have been observed in the human studies due to methodological differences (18). Our results indicate that if Neu4,5Ac 2 is present in substantial amounts in any tissue, an esterase other than NanS must exist to convert Neu4,5Ac 2 to Neu5Ac.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Similar region specificity was observed in the mouse intestine, along with wide variations in sialic acid amounts and their various alternate chemical forms in the liver and central nervous system compared to the intestinal tract (18). Those authors also found substantial amounts of intestinal Neu4,5Ac 2 , which might not have been observed in the human studies due to methodological differences (18). Our results indicate that if Neu4,5Ac 2 is present in substantial amounts in any tissue, an esterase other than NanS must exist to convert Neu4,5Ac 2 to Neu5Ac.…”
supporting
confidence: 65%
“…Our results indicate that if Neu4,5Ac 2 is present in substantial amounts in any tissue, an esterase other than NanS must exist to convert Neu4,5Ac 2 to Neu5Ac. However, in addition to the potentially large amounts of Neu4,5Ac 2 reported in studies of the mouse intestine, the level of Neu5,9Ac 2 in this tissue was reportedly low compared to levels in the human intestine (18). If these differences are real instead of just methodological artifacts, our current results indicate that the mouse would not be a relevant model for investigating enteric colonization of the human intestine in terms of sialometabolism.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…The observed increasing gradient of sialoglycoconjugates from proximal to distal colon agrees with the results reported for pig (Brunsgaard, 1998), human (Robbe et al, 2003), and rat (Accili et al, 2008). In addition, the heterogeneous distribution and structural features of sialoglycoconjugates have been showed in mouse and rat (Karlsson et al, 1997;Rinninger et al, 2006;Accili et al, 2008). The functional meaning of sialylated glycoconjugates, which cause a high negative charge density, may be related to the viscoelastic properties of intestinal mucins as well as the regionspecific colonization of bacteria in the intestine (Robbe et al, 2003) in the requirement of a protective and lubricant action played by these substances (Accili et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…TgMIC13 bound to 4-O-acetylated sialyllactose and a2-9-linked disiayl sequences, which were not recognised by TgMIC1 or NcMIC1. The 4-O-acetyl-substituted sialic acid has been described in various tissues in mice, especially in the gut; its presence has been documented in a number of other animal species and in trace amounts in humans (Iwersen et al, 2003;Rinninger et al, 2006). Information concerning the occurrence of 2-9-linked sialic acid in animals is limited.…”
Section: Importance Of Sialic Acids In Host Invasion By Coccidiansmentioning
confidence: 99%